Detail Exhibit in Quarries - Shodiyev Ramshid Mukhtorvich; Khushvaqtov Asadbek Saydullayevich; Turdiyeva Marjona Abdiholiqovich (Genius Journals, 2024)
The details are taken from the points of the network. The location and working area of the upper and lower limits of the level in Syomka, drainage devices, cutting trenches, underground pits intended for blasting, geological disturbances, sampling sites in geological prospecting pits, transport routes and tracks, etc. The location of buildings, buildings, etc. is determined.
Keywords: Symka; step; lower limits; working area